Managing airway distress in a 2-month-old infant with epiglottic cyst - Hamida, Deta; Olivia Claudia , Pelealu (PERHATI-KL, 2024)
Background: Epiglottic cysts, although rare, are significant causes of neonatal airway obstruction, necessitating prompt recognition and intervention. Purpose: To emphasize the importance of accurate diagnosis and management of airway distress. Case report: A two-month-old infant exhibited persistent tachypnea, inspiratory stridor, and intercostal retractions. Initially misdiagnosed as severe pneumonia, the infant’s condition did not improve with antibiotics. Video-assisted laryngoscopy revealed an obstructive cyst on the epiglottis, which was successfully managed by aspiration, resulting in significant clinical improvement. Clinical question: What are the most effective diagnostic and therapeutic approaches for managing epiglottic cysts in neonates? Method: Thirteen published cases of epiglottic and other laryngeal cysts in neonates, were analyzed, focusing on their clinical presentations, diagnostic methods, management strategies, and outcomes. Data were extracted and summarized in a table for comparison. Result: The review identified common symptoms, including respiratory distress and feeding difficulties. Initial misdiagnosis was prevalent, with many cases attributed to pneumonia or laryngomalacia. Video-assisted laryngoscopy emerged as the gold standard for diagnosis, supplemented by CT and MRI. Management varied from cyst aspiration to endoscopic ablation and microsurgical excision, with positive outcomes in most cases. The objective was to summarize the findings in a review manner, highlighting trends and commonalities among the cases. Conclusion: The successful management of this case through cyst aspiration highlighted the importance of timely and accurate diagnosis, and the necessity for standardized diagnostic and therapeutic protocols. Future research should aim to refine diagnostic criteria and develop consensus guidelines, to enhance patient outcomes in this vulnerable population. Keywords: epiglottic cysts, neonatal airway obstruction, respiratory distress, video-assisted laryngoscopy ABSTRAK Latar belakang: Kista epiglotis, meskipun jarang, merupakan penyebab signifikan obstruksi saluran napas pada neonatus, yang memerlukan pengenalan dan intervensi yang cepat. Tujuan: Untuk menekankan pentingnya diagnosis dan penatalaksanaan akurat. Laporan kasus: Bayi berusia dua bulan menunjukkan takipnea persisten, stridor inspiratorik, dan retraksi interkostal. Awalnya salah didiagnosis sebagai pneumonia berat, dan kondisi bayi ini tidak membaik dengan pemberian antibiotik. Video-laringoskopi mengungkapkan adanya kista obstruktif pada epiglotis, yang berhasil dikelola dengan aspirasi, dan menghasilkan perbaikan klinis yang signifikan. Pertanyaan klinis: Apa pendekatan diagnostik dan terapeutik yang paling efektif untuk mengelola kista epiglotis pada neonatus? Metode: Tigabelas kasus yang dipublikasikan tentang kista epiglotis dan kista laring lainnya pada neonatus dianalisis, dengan fokus pada presentasi klinis, metode diagnostik, strategi penatalaksanaan, dan hasilnya. Data diekstraksi dan dirangkum dalam tabel untuk perbandingan. Hasil: Tinjauan ini mengidentifikasi gejala umum, termasuk kesulitan bernapas dan kesulitan pemberian makan. Diagnosis awal kerap kali salah, dengan banyak kasus yang dianggap berhubungan dengan pneumonia atau laringomalasia. Video-laringoskopi muncul sebagai standar emas untuk diagnosis, dilengkapi dengan CT dan MRI. Penatalaksanaan bervariasi dari aspirasi kista hingga ablasi endoskopik dan eksisi bedah-mikro, dengan hasil positif pada sebagian besar kasus. Hasil temuan dirangkum dalam bentuk tinjauan, menyoroti gejala klinis dan kesamaan di antara kasus-kasus tersebut. Kesimpulan: Penatalaksanaan yang berhasil dari kasus ini melalui aspirasi kista, menitikberatkan pentingnya diagnosis yang tepat waktu dan akurat, serta kebutuhan akan protokol diagnostik dan terapeutik yang terstandarisasi. Penelitian di masa depan harus bertujuan untuk memperbaiki kriteria diagnostik, dan mengembangkan pedoman konsensus, untuk meningkatkan keberhasilan menolong pasien dalam populasi yang rentan ini. Kata kunci: kista epiglotis, obstruksi saluran napas neonatus, kesulitan bernapas, video- laringoskopi